Performance of UC Davis Chimney Dryer on Drying and Quality of Different Vegetables. - Islam, M. Ashraful. (Tufts University. Tisch Library., 2020)
This presentation descibes the presenter's experiment on testing the UC Davis Solar Chimney Dryer in Bangladesh.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy